2000
DOI: 10.3310/hta4070
|View full text |Cite
|
Sign up to set email alerts
|

Implantable contraceptives (subdermal implants and hormonally impregnated intrauterine systems) versus other forms of reversible contraceptives: two systematic reviews to assess relative effectiveness, acceptability, tolerability and cost-effectiveness.

Abstract: et al. Implantable contraceptives (subdermal implants and hormonally impregnated intrauterine systems) versus other forms of reversible contraceptives: two systematic reviews to assess relative effectiveness, acceptability, tolerability and cost-effectiveness. Health Technol Assess 2000;4(7). Health Technology Assessment is indexed in Index Medicus/MEDLINE and Excerpta Medica/ EMBASE. Copies of the Executive Summaries are available from the NCCHTA website (see overleaf). NHS R&D HTA Programme T he overall aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(33 citation statements)
references
References 124 publications
(243 reference statements)
0
32
0
1
Order By: Relevance
“…The only significant difference is the LNG-IUS doubles the incidence of moodiness. A systematic review has identified no differences in side-effects (acne, headaches, breast tenderness, nausea, prolonged bleeding, embedded device and pelvic inflammatory disease) between LNG-IUS and IUD 24 . Although serum levonorgestrel levels are low in LNG-IUD users (compared with oral or subdermal administration), wide inter-individual differences in systemic absorption of levonorgestrel occur 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only significant difference is the LNG-IUS doubles the incidence of moodiness. A systematic review has identified no differences in side-effects (acne, headaches, breast tenderness, nausea, prolonged bleeding, embedded device and pelvic inflammatory disease) between LNG-IUS and IUD 24 . Although serum levonorgestrel levels are low in LNG-IUD users (compared with oral or subdermal administration), wide inter-individual differences in systemic absorption of levonorgestrel occur 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The rate of teenage pregnancy and termination of pregnancy is amongst the highest in the UK. Of concern, this rate is increasing (an absolute increase of 28% in pregnancies in [13][14][15][16][17][18][19][20][21][22][23][24][25] year age group from 2002 to 2003), with a corresponding increase in abortions 12 . Therefore, it is important that Fife has an effective contraceptive service.…”
Section: Introductionmentioning
confidence: 99%
“…This is known as the "Pearl index." Both the newer copper-containing devices and the levonorgestrel-releasing device are effective methods of contraception, with a Pearl index of less than 1 per 100 woman-years [2].…”
Section: Discussionmentioning
confidence: 99%
“…Low ectopic pregnancy rates of 0.25/1000 woman-years are reported with use of modern copper devices containing more than 350 mm 2 of copper (CuT380) 21 . The LNG IUS has even lower ectopic pregnancy rates compared to modern copper IUDs 22,23 .…”
Section: Does Past Use Of Iuds Increase the Risk Of Ectopic Pregnancy?mentioning
confidence: 99%
“…Copper IUDs also provide a far more effective option than condoms/diaphragms for women not wishing to use hormonal methods. Cumulative pregnancy rates of 1.4-2.7/100 womanyears are reported with CuT380, Multiload Cu375 Ò and GyneFix Ò21, 22 . Other benefits are that no user motivation is required, there are no systemic metabolic effects and a rapid return to pre-existing fertility occurs.…”
Section: Does Past Use Of Iuds Increase the Risk Of Ectopic Pregnancy?mentioning
confidence: 99%